Performance Evaluation of Reactive Routing Protocols Using IEEE 802.15.4 Application in Designed Wireless Sensor Network - Payal; Sharma, D; Kumar, S (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Networks (WSN’s) are decentralized type of networks used in sensing and processing physical data without any pre-existing infrastructure. WSN consists of sensing nodes that can interact among themselves and with the physical environment for sensing, measuring and controlling various parameters. For effective and efficient transmission of information in a seamless manner, the choice of routing protocol is still a major constraint in WSN design. In this paper, Reactive Routing protocols using IEEE 802.15.4 application have been evaluated on the designed network scenario. The parameters we have used are (i) Throughput (ii) AEED (iii) Number of Packets Forwarded (iv) Number of Packets Dropped as performance metrices in both Static and Mobile environment for 50, 75 and 100 nodes.